2021
DOI: 10.1016/j.ebiom.2021.103638
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory dysfunction is masked by variable cognitive deficits across patients on the Alzheimer's disease spectrum

Abstract: Background: Alzheimer's disease (AD) is generally thought to spare primary sensory function; however, such interpretations have drawn from a literature that has rarely taken into account the variable cognitive declines seen in patients with AD. As these cognitive domains are now known to modulate cortical somatosensory processing, it remains possible that abnormalities in somatosensory function in patients with AD have been suppressed by neuropsychological variability in previous research. Methods: In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…To address how morphological phenotypes differ between microglia across brain regions, we immunostained the adult C57BL/6J mouse brain with the allograft inflammatory factor 1 (Aif1/Iba1) 16 for both sexes with at least biological triplicates. Then, we traced 9,997 cells and generated a library of 3D microglial skeletons from seven brain regions chosen to span the rostrocaudal axis with a preference for regions that are known to be affected in Alzheimer disease [17][18][19][20][21][22][23] : the olfactory bulb (OB mg ), frontal cortex (FC mg ), dentate gyrus of the hippocampus (DG mg ), primary somatosensory cortex (S1 mg ), substantia nigra (SN mg ), cochlear nucleus (CN mg ) and cerebellum (CB mg ; Fig. 1a).…”
Section: Morphomics Uncovers Adult Microglial Heterogeneitymentioning
confidence: 99%
“…To address how morphological phenotypes differ between microglia across brain regions, we immunostained the adult C57BL/6J mouse brain with the allograft inflammatory factor 1 (Aif1/Iba1) 16 for both sexes with at least biological triplicates. Then, we traced 9,997 cells and generated a library of 3D microglial skeletons from seven brain regions chosen to span the rostrocaudal axis with a preference for regions that are known to be affected in Alzheimer disease [17][18][19][20][21][22][23] : the olfactory bulb (OB mg ), frontal cortex (FC mg ), dentate gyrus of the hippocampus (DG mg ), primary somatosensory cortex (S1 mg ), substantia nigra (SN mg ), cochlear nucleus (CN mg ) and cerebellum (CB mg ; Fig. 1a).…”
Section: Morphomics Uncovers Adult Microglial Heterogeneitymentioning
confidence: 99%
“…To identify the impact of Alzheimer’s disease and HAND pathologies on somatosensory gating and be consistent with previous studies, 13 , 14 , 40 we computed the gating ratio (i.e. response to Stimulation 2 divided by the response to Stimulation 1) and ran a 3 × 1 ANOVA.…”
Section: Resultsmentioning
confidence: 85%
“… 82 , 83 Further, one recent study showed that such gating deficits can be obscured by differences in neurocognitive function. 40 Interestingly, this latter study focused on somatosensory gating and involved patients across the Alzheimer’s disease spectrum (i.e. mild cognitive impairment (MCI) and mild Alzheimer’s disease).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For somatosensory paradigms, epochs were of 0.3 s duration, with 0.0 s defined as stimulation onset and the baseline being the −0.05 to 0.0 s window. Epochs containing artifacts were excluded using a fixed threshold method (i.e., based on artifactual neural amplitude values), supplemented with visual inspection ( Christopher-Hayes et al, 2021 , Spooner et al, 2021a , Wiesman et al, 2021 ). Artifact-free epochs were time-domain averaged with respect to movement or stimulation onset.…”
Section: Methodsmentioning
confidence: 99%